Permasalahan Kepadatan Penduduk Terhadap Pemborosan Listrik dengan Solusi Panel Surya di Bandar Selamat, Medan Tembung - Meilinda Suriani Harefa; Syukri Hidayat; Tasya Nasution; Nur Indah Lestari; Poppy Ardian Ningsih Zega; Alan Mustaqim Nst (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of population density on electricity consumption and evaluate the potential use of solar panels as a solution to overcome energy waste in urban areas, especially on Jalan Kapten Muhammad Jamil Lubis, Medan Tembung, Medan, North Sumatra. The method used is qualitative research with a literature study approach, which involves collecting data from various written sources, such as journals, books, and research reports. The results of the study indicate that the high population density in this area contributes to inefficient energy consumption. Factors such as people's habits in using electronic devices, less than optimal energy infrastructure quality, and increased energy demand due to economic activities are the main causes of energy waste. Solar panels are identified as a potential solution to overcome these problems. This technology is able to convert solar energy into electricity efficiently, even in areas with varying weather. In addition to supporting environmental sustainability by reducing carbon emissions, solar panels also utilize empty spaces such as building roofs, making them suitable for densely populated areas such as Medan Tembung. This study concludes that the adoption of solar panels, supported by government regulations, incentives, and community education programs, can be a strategic step in creating a more efficient and environmentally friendly energy system. Further research involving field trials is recommended to support wider implementation of this technology.